2022
DOI: 10.3390/medicina58091207
|View full text |Cite
|
Sign up to set email alerts
|

Is Osteoarthritis Always Associated with Low Bone Mineral Density in Elderly Patients?

Abstract: Background and Objectives: The relationship between osteoarthritis (OA) and osteoporosis (OP) has been analysed for over four decades. However, this relationship has remained controversial. Numerous observational and longitudinal studies have shown an inverse association between the two diseases and a protective effect of one against the other. On the other hand, some studies show that patients with OA have impaired bone strength and are more prone to fractures. The study’s main objective was to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…The age restrictions were introduced in order to exclude mild hip dysplasia (clinical presentation before 55 years of age) [ 28 ], the effect of hormonal changes in the early menopause (50–55 years) over SB [ 34 ], and the high rate of HOA in people over 60 years of age [ 18 , 22 ], as well as due to data regarding life duration (decreasing the chance of successfully finishing the 7-year follow-up period). The restriction in BMI and severe deviations in the weight-bearing axis were introduced in order to eliminate the effect of these variables on the RP of HOA [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The age restrictions were introduced in order to exclude mild hip dysplasia (clinical presentation before 55 years of age) [ 28 ], the effect of hormonal changes in the early menopause (50–55 years) over SB [ 34 ], and the high rate of HOA in people over 60 years of age [ 18 , 22 ], as well as due to data regarding life duration (decreasing the chance of successfully finishing the 7-year follow-up period). The restriction in BMI and severe deviations in the weight-bearing axis were introduced in order to eliminate the effect of these variables on the RP of HOA [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Over the past 40 years, researchers have tried to determine the relationship between BMD and the progression of clinical and morphological changes in HOA [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, most studies have reported somewhat contradictory data, such as an association between HOA and increased or decreased BMD, both on a local level (PF-BMD) [ 10 , 11 , 15 , 18 , 22 ] and in the whole body (TB-BMD) [ 12 , 13 , 14 , 16 , 17 , 18 ], including patients with advanced HOA waiting for THR [ 19 , 20 , 21 ]. In the cited studies [ 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], the effect of several important factors was not taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower-extremity OA, especially in postmenopausal women, is complicated by OP. Stamenkovic et al demonstrated that in postmenopausal women, the BMD grade and T-score of the spine and femoral neck are low in more severe forms of OA [23]. Postural changes identified in postmenopausal women have been associated with bone loss and joint degeneration [114].…”
Section: Low Bone Mineral Density and Osteoarthritismentioning
confidence: 99%
“…High bone mineral density (BMD) has been implicated in OA pathophysiology [18][19][20], and OA and OP were initially considered incompatible and contrary pathologies. Conversely, osteoporotic fractures in patients with lower-extremity OA (HOA and KOA) and the development of OA progression in patients with OP are being reported increasingly [21][22][23]. Subchondral insufficiency fracture (SIF), which is based on bone fragility and often causes irreversible deformity and significant ADL loss, has gradually been clarified.…”
Section: Introductionmentioning
confidence: 99%